Analisis Tanggung Jawab Hukum Operator Telekomunikasi Atas Kebocoran Data Pribadi Dalam Kasus Recycle Nomor Ponsel di Indonesia (LEGAL DIALOGICA, 2025)
This study aims to analyze the legal liability of telecommunications operators regarding the leakage of consumers' personal data resulting from the practice of SIM card recycling in Indonesia. This issue has become increasingly relevant due to the rising number of personal data misuse cases stemming from phone numbers that have been reassigned to new users without adequate data erasure systems. The research employs a normative juridical approach by examining the applicable laws and regulations as well as concrete cases as secondary data. The findings indicate that telecommunications operators bear legal responsibility for negligence in securing customer data, and may be subject to administrative sanctions, compensation claims, or even criminal penalties pursuant to Law Number 27 of 2022 on Personal Data Protection and Law Number 8 of 1999 on Consumer Protection. The study recommends the formulation of strict standard operating procedures (SOPs) for the SIM card recycling process, as well as the need for strengthened oversight by the relevant authorities.Abstrak:Penelitian ini bertujuan untuk menganalisis tanggung jawab hukum operator telekomunikasi terhadap kebocoran data pribadi konsumen yang terjadi akibat praktik daur ulang nomor ponsel (SIM card recycling) di Indonesia. Permasalahan ini menjadi semakin relevan mengingat meningkatnya kasus penyalahgunaan data pribadi yang bersumber dari nomor ponsel yang telah dialihkan ke pengguna baru tanpa sistem penghapusan data yang memadai. Penelitian ini menggunakan pendekatan yuridis normatif dengan menelaah peraturan perundang-undangan yang berlaku serta kasus-kasus konkret sebagai data sekunder. Hasil penelitian menunjukkan bahwa operator telekomunikasi memiliki tanggung jawab hukum atas kelalaian dalam mengamankan data pelanggan, yang dapat dikenai sanksi administratif, ganti rugi, hingga pidana sesuai dengan Undang-Undang Nomor 27 Tahun 2022 tentang Pelindungan Data Pribadi dan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Penelitian ini merekomendasikan penyusunan standar operasional prosedur (SOP) yang ketat dalam proses daur ulang nomor ponsel serta perlunya penguatan pengawasan oleh otoritas terkait.